DEVELOPMENT OF THE REPRODUCTIVE HEALTH MODEL AS A PREVENTION EFFECT OF ADOLESCENT PREGNANCY: REVIEW ARTICLE - Panjaitan, Arip Ambulan (JOURNAL OF RESEARCH IN PUBLIC HEALTH SCIENCES, 2019)
Introduction: Adolescent reproductive health problems are an international problem. Circumstances that occur in Indonesia, young women are more afraid of social risks such as virginity loss, extramarital pregnancies that will be a source of public gossip compared to sexual risk, which concerns reproductive health and sexual health. This study aims to collect and analyze articles relating to the development of reproductive health models based on needs, needs, schools, culture and family as an effort to prevent pregnancy in adolescents. Methods: The method used is literature review, articles are collected using search engines such as EBSCO, Sciencedirect, googlesholar. The criteria for the articles used are those published in 1995-2018. Result: Based on the results that the reproductive health situation of young women is a problem behind the still high maternal and infant mortality rates. This condition is exacerbated by other factors such as early marriage, early pregnancy, STIs, HIV and AIDS and non-communicable diseases such as breast and cervical cancer, abortion, premarital sex, nutrition and others. Exposure of adolescent girls to reproductive health from the social environment about health education through adolescent approaches involving peers, BK teachers, family or parents, health workers and stakeholders. Information about reproductive health issues, besides being important to be known by health care providers, decision makers, is also important for stakeholders, so that they can help reduce reproductive health problems for young women.